Pemenuhan Pekerjaan Dan Penghidupan Yang Layak Di Masa Bonus Demografi - Desty Puteri Hardyati; Hilman Rigel Nugroho; Neshafi Laudza Rahardian; Ria Karlina Lubis (Peneliti.net, 2023)
The Central Bureau of Statistics predicts that Indonesia will be in a demographic bonus period in 2030. This year is the same year as the year the goal of achieving the goal of creating decent work and economic growth goals. The real problem that arises when the state is unable to manage the demographic bonus is the high unemployment rate. The results of the study show that the problems of fulfilling decent work and livelihoods during the demographic bonus period can be answered by fulfilling decent work indicators in Goal 8 of the Sustainable Development Goals Decent Work and Economic Growth. Indicators of success are the opening of MSME access and job creation. Goal 8 of TPB views that developing MSMEs can create jobs. So as to be able to accommodate employment during the demographic bonus period. Its manifestation in Indonesia can be seen in the UMKM optimization policy which is supported by the work copyright law. This regulation is expected to be able to answer the challenges of labor market competition. The government views that through the ease of investment in MSMEs it will open up many jobs and help improve the ability of the workforce later. When looking at the fulfillment of decent work in 2030 with the SDGs indicator, it appears that Indonesia is ready to face the challenges of employment during the demographic bonus period. The research was conducted using normative juridical methods by collecting secondary data. The approach used in this study is a statutory and conceptual approach. The results of data analysis will be described descriptively.